Penyusunan Ensiklopedia Berbasis Identifikasi Morfologi Dan Anatomi Tumbuhan Paku (Pteridophyta) Di Kawasan Jalur Pendakian Gunung Lawu Via Cemoro Kandang - Fitri Rohmah Sari; Bekti Kiswardianta; Nurul Kusuma Dewi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
Research has been carried out in March-June 2021 on the Mount Lawu climbing route via Cemoro cage starting from the entrance gate to an altitude of 2100 meters above sea level. This study aims to analyze various kinds of Pteridophyta species diversity found in Cemoro Kandang, Mount Lawu, Observing Anatomy, Studying the condition of physicochemical parameters and making learning support media in the form of encyclopedias obtained from observations and research. Observation of Pteridophyta using plot method and roaming method. Pteridophyta retrieval using the plot method, carried out by making 5 stations first, then plotting 5x5 m2. This collection aims to represent plants found in a community on the hiking trail of Mount Lawu via Cemoro cage. While the cruising method is used to retrieve documentation along the hiking trail. Data analysis carried out included abundance, diversity index, physicochemical parameters, and module making. Based on the research data, various ferns (pteridophytes) both epiphytes and terrestrial plants with a total of 18 species from 3 stations were divided into 7 epiphytic plants Davallia denticulata (Burm. ) mett. Belviacia revoluta (BI.) Copel. Phymatodes scolopendria (Burm.) Ching. Asplenium adiantoides (L) C. Chr. Elaphoglossum tonduzii Christ. Crypsinus enervis (Cav.) Copel. Vittaria elongata sw. 11 terrestrial plants Polystichum aculeatum (L) Roth ex Mert. Dennstaedtia punctilobula (Michx.) T. Moore. Chingia sakayensis (Zeiler) Holtt. Adiantum pedatum. Pteridium aquilinum (L). Khun. Gleichenia linearis (Burm.) Clarke. Athyrium asperum (BI.) Milde. Pteris Muricella Fee. Cyathea sp. Blenhnum orientale L. hypolepis brooksiae v.A.v.R. Species diversity is calculated by counting the number of important value indexes. The highest INP diversity of Pteridophyta Belviacia revoluta (BI.) Copel. With an INP value of 47.6. The results of the physicochemical parameters showed an average air temperature of 18.3°C, light intensity 752Lux, humidity 74% RH, soil pH 7.3, soil moisture 1%. The results of the analysis of the Encyclopedia that have been validated show that it is